Research progress of viral sepsis: etiology, pathophysiology, diagnosis, and treatment - Jianping Li; Yiqi Luo; Hao Li; Yunhong Yin; Yi Zhang (Emergency and Critical Care Medicine)
Abstract. Sepsis is a common systemic disease characterized by various physiological and pathological disorders. It can result from infection by various pathogens, such as bacteria, viruses, and fungi. The rate of culture-negative sepsis is almost 42%, indicating that most patients may have nonbacterial infections. With the outbreak of coronavirus disease 2019, viral sepsis has attracted growing attention because many critically ill patients develop sepsis. Viral sepsis can be caused by viral infections and combined with, or secondary to, bacterial infections. Understanding the common types of viral sepsis and the main characteristics of its pathogenesis will be helpful for effective diagnosis and treatment, thereby reducing mortality. Early identification of the causative agent of viral sepsis can help reduce the overuse of broad-spectrum antibiotics. In this article, we reviewed the common viruses of sepsis, their potential pathophysiology, targets of diagnosis, and remedies for viral sepsis.